CALCULATION OF GATING SYSTEM FOR INPUT OF METAL INTO CRYSTALLIZER - A. M. Bodjako; P. I. Zimonin; I. A. Melnikov; A. A. Suponev (Литьë и металлургия)
The calculation dependencies for determination of the main constructive parameters of metal wire for production of slugs of  different dimension-type by means of continuously-cyclic casting by frosting are received.